Mapping of Dairy Cattle Farms District of Boyolali Using Webgis - Listyani Nurmawati, Elly; , Helman Muhammad, S.T., M.T (2015)
As the development of technology will be able to facilitate the organizations and institutions to improve performance in order to more effectively and efficiently Based on this it will be designed and built a "MAPPING OF DAIRY CATTLE FARMS DISTRICT OF BOYOLALI USING WEBGIS". This system is built using waterfall method, with software applications is quantum gis and then the output WebGIS which can display information about dairy cattle Boyolali. WebGIS is built with PHP, while for managing MySQL database in default of xampp Geographic Information System is able to facilitate the public to obtain information dairy cow milk in Boyolali. Keyword : GIS, Cattle, quantum gis